A Laboratory Investigation into the Effects of Coarse Aggregate Angularity on Performance of WMA - Jie Ji; Peng Zhai; Wenhua Zheng; Zhi Suo; Ying Xu (Advances in Materials Science and Engineering)
This study evaluated the effects of coarse aggregate angularity (CAA) on the performances of warm mix asphalt (WMA) because previous studies have predominantly focused on the effects of CAA on the hot mix asphalt (HMA) performances. Five different CAAs were fabricated using Los Angeles abrasion test, and the digital image processing method was used to identify the CAA. Five mixes with different combinations of CAA and Sasobit-modified asphalt binder were prepared according to the Marshall mix design procedure. The performances such as the resistance to rutting and thermal cracking, moisture susceptibility, and volumetric characteristics of WMA were evaluated. The test results indicated that the CAA value was linearly declined with the abrasive wearing passes increased. Higher CAA value improved the potential to resistance to rutting of WMA but was not suitable to enhance the resistance to thermal cracking of WMA due to sharp corners that caused higher stress concentration. In addition, WMA was more prone to develop numerous macrocracking, which resulted in lower moisture susceptibility due to higher CAA value inducing higher air void, VMA, and VCA of WMA.